(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2013)
In a previous study children responded by exclusion in a matching to sample procedure (MTS), but not all learned the relationships between names and objects after a single exclusion trial. Aiming to investigate exclusion responding on teaching to read words in a play setting after a single exclusion trial, and test the efficacy of this procedure to develop reading words formed by the recombination of syllables, five children with a history of school failure were submitted to a MTS procedure. All participants chose by exclusion, learned new conditional relations between written words and spoken words after a single exclusion trial, and were able to read some of the words of the generalization test. These results show that responding by exclusion on a MTS procedure was effective to: teach new conditional relations in a single trial, and to establish partial control by syllables.